2010
DOI: 10.1037/a0017357
|View full text |Cite
|
Sign up to set email alerts
|

Predicting levels of Latino depression: Acculturation, acculturative stress, and coping.

Abstract: Past research has noted that aspects of living in the United States place Latinos at risk for experiencing psychological problems. However, the specific features of the adaptation process that contribute to depression remain unclear. The purpose of the present study was to investigate the ability of acculturation, acculturative stress, and coping to predict membership into low, medium, and high groups of depression among Latinos. Within a group of 148 Latino adults from the community, a multinomial logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
200
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(219 citation statements)
references
References 52 publications
15
200
2
2
Order By: Relevance
“…The average traumatic stress symptoms fell in the mild to moderate levels. As for depression, CES-D mean scores were in the moderate to high range and just below a commonly used clinical cut-off (CES-D score ≥16; Torres, 2010). Traumatic stress and depression was found to be significantly correlated.…”
Section: Resultsmentioning
confidence: 93%
“…The average traumatic stress symptoms fell in the mild to moderate levels. As for depression, CES-D mean scores were in the moderate to high range and just below a commonly used clinical cut-off (CES-D score ≥16; Torres, 2010). Traumatic stress and depression was found to be significantly correlated.…”
Section: Resultsmentioning
confidence: 93%
“…A recent review of the impact of depression on workforce productivity 16) found a mediating effect of job stressors on depression and pointed out lack of studies that evaluated whether job stressors play a role as a mediating factor for depression. Taken together with previous studies aforementioned 3,9,12,13,15) , acculturative stress would lead indirectly to depression by increasing job-related stress; however, no empirical evidence supporting this pathway has been found. In KoreanChinese migrant workers with rare opportunities for health promotion service at work, a community-based approach would be a feasible and necessary alternative way to decrease acculturative stress, which consequently leads to a decrease in job stress and depression.…”
mentioning
confidence: 74%
“…This cognitive theory provides a theoretical basis to explain depressive phenomena among migrant population and also serves as a basis for Berry's 11) acculturative stress model. It is important to note that acculturative stress was found to be a significant contributor to depression in other ethnic groups 3,12) . The complex acculturation process, including language acquisition and changes in behavior, identity and values, has been measured extensively among immigrant populations 27) ; however, Asian countries have remained ethnically homogeneous until recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations